Use of image analysis in the study of competition between filamentous and non-filamentous bacteria - Contreras, Edgardo Martin (2004)
One of the most common problems in the operation of activated sludge plants is the inability to separate solids from treated efﬂuents in the clariﬁers caused by the overgrowth of ﬁlamentous micro-organisms (FM) with respect to ﬂoc-forming bacteria. In order to develop kinetic models that help to predict bulking events, growth kinetics of the FMs and non-ﬁlamentous bacteria (NFB) should be known. This paper addresses the competition of a FM and a NFB in a continuous stirred tank reactor. Experimental observations of the effect of the dilution rate on the composition of themixed culture were compared to simulated results. Image analysis was used to measure NFB and FM fractions in order to evaluate the proposed mathematical model. Experimental results and numerical simulations showed that low D values favored the growth of FM; on the contrary, when high D values were applied a rapid overgrowth of the NFB were observed. Thus, high D values favored the growth of NFB minimizing the risk of ﬁlamentous bulking.